2002
DOI: 10.1542/peds.110.6.e68
|View full text |Cite
|
Sign up to set email alerts
|

Physician Perspectives Regarding Pneumococcal Conjugate Vaccine

Abstract: ABSTRACT. Objectives. Pneumococcal conjugate vaccine (PCV) was first licensed for routine administration to young children in February 2000. The objective of this study was to assess physician perspectives about the use of PCV, to ascertain which children were being given the vaccine soon after licensure, and to determine how the addition of PCV to the schedule of recommended childhood vaccines may affect the timing of other vaccinations.Methods. A 30-item survey containing questions about the use of PCV was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 24 publications
(10 reference statements)
2
25
0
Order By: Relevance
“…Although the number of pediatrics practices was relatively small in the study counties, we did not find that pediatricians were much more likely to carry HPV vaccine than family practitioners, as has been observed soon after introduction of several childhood vaccines [9][10][11]. Few internal medicine practices had the vaccine; however, 64% of obstetrics-gynecology practices offered it.…”
Section: Discussionmentioning
confidence: 70%
“…Although the number of pediatrics practices was relatively small in the study counties, we did not find that pediatricians were much more likely to carry HPV vaccine than family practitioners, as has been observed soon after introduction of several childhood vaccines [9][10][11]. Few internal medicine practices had the vaccine; however, 64% of obstetrics-gynecology practices offered it.…”
Section: Discussionmentioning
confidence: 70%
“…As with other studies on the adoption of new vaccines, [24][25][26] there were important differences between family medicine physicians and pediatricians in practices and attitudes regarding rotavirus vaccine. Although both specialties are more likely to administer rotavirus vaccine now than they were 5 years ago, pediatricians are substantially more likely to use the vaccine, report a higher level of confidence in the effectiveness of rotavirus vaccine, and feel favorable about the vaccine.…”
Section: Discussionmentioning
confidence: 71%
“…However, communicating the risks and benefits of vaccines does not always meet parents' needs because a number of pediatricians do not accept patients whose parents refuse vaccination, and pediatricians' knowledge of infant vaccination recommendations is generally quite poor [5]. Various studies have clearly demonstrated that, particularly when new vaccines are included in the immunization schedules recommended by health authorities, pediatricians do not always know the schedules themselves or the related contraindications and this may contribute towards increasing the number of missed opportunities to immunize [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%